Analysis of Carrying Capacity of Agro-Ecosystem Coconut-Cattle in South Minahasa Regency - Salendu, AHS; Maryunani, Maryunani; Soemarno, Soemarno; Polii, B (ANIMAL PRODUCTION, 2012)
Abstract. Coconut plantation is very dominating in South Minahasa regency seen from its production of 49,907.33 tons in 2010. The land under coconut trees can be used for food crops or forage. The waste from food crops is the source of animal feed, while the livestockâs manure is used to improve soil fertility under coconut tree. The research objective was to analyse the carrying capacity of the agro-ecosystem of coconut-cattle. Regency and district were determined purposively. A total of 86 farmers as respondents were determined based on the ownership of at least 2 cattle and cattle selling experience. Data were analyzed using effective potential of livestock development and land capability index (IDD). The result showed that the maximum potential of land resources (PMSL) was 30,872.94 animal unit (AU). The capacity increase in cattle population based on the soil resources was 18,208.94 AU. The maximum potential based on farmer house holds was 127,023.00 AU. The value of land capability index was 2.14. The conclusion was South Minahasa Regency was still potential for cattle development regarding land resources or workforce potentials. Development of cattle can be integrated with the coconut to maintain and improve agro-ecosystem sustainability of coconut plantation.Keywords: cattle, carrying capacity, agro-ecosystem, coconutAnimal Production 14(1):56-62, January 2012